Marine yeasts and bacteria as biological control agents against anthracnose on mango. Issue 11 (18th September 2017) - Hernandez Montiel, Luis G.; Zulueta Rodriguez, Ramon; Angulo, Carlos; Rueda Puente, Edgar O.; Quiñonez Aguilar, Evangelina E.; Galicia, Ricardo
Abstract: The potential of four yeasts ( Debaryomyces hansenii, Rhodotorula minuta, Cryptococcus laurentii and Cryptococcus diffluens ) and three bacteria ( Bacillus amyloliquefaciens, Bacillus subtilis and Stenotrophomonas rhizophila ) with antagonistic capacity against anthracnose caused by Colletotrichum gloeosporioides in mango cv. Ataulfo fruit was investigated. Germination of C. gloeosporioides spores was significantly inhibited by all marine yeasts and bacteria strains of an in vitro test. When yeasts and bacteria were tested on mango fruit, the marine yeast D. hansenii 1R11CB strain and marine bacteria S. rhizophila KM02 strain were the best antagonists to anthracnose ( C. gloeosporioides ), which significantly decreased disease incidence by 56% and 89%, respectively, and reduced lesion diameter by 91% and 92%, respectively. All the isolated strains of the phytopathogen, yeasts and bacteria were molecularly identified. Our results from in vitro and in vivo experiments suggest that marine yeasts and bacteria strains can be used as some effective biological control agents for anthracnose in mango.